Analisis Peran Persepsi Mahasiswa Mengenai Pendidikan Kewarganegaraan Dalam Memajukan Ekonomi : (Studi Kasus Mahasiswa Unimed) - Ira Yenita Malau; Maida Puspa Ristika Ambarita; Meliana Girsang; Rani Sabeta Nainggolan; Dina Pratiwi Tambunt; Teddy Pascha Depariy; Fazli Rachman (Public Service and Governance Journal, 2024)
This research uses a case study method approach to analyze student perceptions about citizenship education and its impact on economic progress. Citizenship education is an important component in the development of individuals as responsible citizens, and has the potential to influence a country's economic sector. In this research, we conducted surveys and interviews with students from various backgrounds and majors at a university. The data obtained revealed diverse perceptions about citizenship education and how understanding of social and political issues influences their views about individual contributions to economic progress. The results of this research can provide valuable insight into the role of citizenship education in shaping students' thinking about economic progress and how such education can be improved to more effectively prepare students to become active and productive citizens in driving the country's economic growth. This research also identifies the potential for collaboration between educational institutions and the economic sector to advance a more effective and relevant citizenship education agenda.